-7(x+2)-43=6-14

Simple and best practice solution for -7(x+2)-43=6-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+2)-43=6-14 equation:

Simplifying
-7(x + 2) + -43 = 6 + -14
Reorder the terms:
-7(2 + x) + -43 = 6 + -14
(2 * -7 + x * -7) + -43 = 6 + -14
(-14 + -7x) + -43 = 6 + -14
Reorder the terms:
-14 + -43 + -7x = 6 + -14
Combine like terms: -14 + -43 = -57
-57 + -7x = 6 + -14
Combine like terms: 6 + -14 = -8
-57 + -7x = -8
Solving
-57 + -7x = -8
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '57' to each side of the equation.
-57 + 57 + -7x = -8 + 57
Combine like terms: -57 + 57 = 0
0 + -7x = -8 + 57
-7x = -8 + 57
Combine like terms: -8 + 57 = 49
-7x = 49
Divide each side by '-7'.
x = -7
Simplifying
x = -7`